Efforts to Improve Learning Outcomes of Islamic Religious Education Through Cooperative Learning at Madrasah Aliyah Al-Wathoniyah 20 - Mochammad Zaedan; Marhamah (CV ODIS, 2023)
This study aims to analyze efforts to improve learning outcomes in Islamic Religious Education through the application of the Cooperative Learning method at Madrasah Aliyah. Islamic Religious Education has an important role in forming the character and religious values of students, therefore, improving learning outcomes in this subject is very important. The Cooperative Learning method has been recognized as an effective approach to improving learning outcomes and developing students' social skills. This study used an experimental research design with a control group and an experimental group at Madrasah Aliyah. Data was collected through learning achievement tests before and after the application of the Cooperative Learning method. The results of the data analysis showed that the experimental group that took part in learning with the Cooperative Learning method experienced a significant increase in learning outcomes in Islamic Religious Education compared to the control group that received conventional learning. These findings indicate that the application of the Cooperative Learning method can be an effective strategy for improving the learning outcomes of Islamic Religious Education at Madrasah Aliyah. The implication of this research is the importance of developing more interactive and collaboration-oriented learning methods in the context of religious education to increase students' understanding and involvement in this subject.